Cold-related symptoms and performance degradation among Thai poultry industry workers with reference to vulnerable groups: a cross-sectional study - Nipaporn Auttanate (2020)
BACKGROUND: Few studies have examined cold-related symptoms among cold workplace workers in Thailand. This study aimed to determine the prevalence of cold-related cardiorespiratory, circulatory, and general symptoms and performance degradation among Thai chicken industry workers and identify vulnerable groups. METHODS: Overall, 422 workers aged from 18 to 57 years at four chicken meat factories in Thailand were interviewed for cold-related symptoms and complaints. The results were expressed in terms of model-based adjusted prevalence and prevalence differences (PDs) in percentage points (pp) with 95% confidence intervals (CIs). RESULTS: In total, 76.1% of the respondents reported cold-related respiratory symptoms, 24.6% reported cardiac symptoms, 68.6% reported circulatory symptoms, and 72.1% reported general symptoms. In addition, 82.7% of the respondents reported performance degradation. Cold-related respiratory symptoms increased by PD 29.0 pp. (95% CI 23.4-34.6) from the lowest to the highest educational group, with a similar pattern observed in performance degradation. Forklift drivers and storage and manufacturing workers complained of cold-related respiratory symptoms more than office staff (PD 22.1 pp., 95% CI 12.8-31.3; 12.0 pp., 95% CI 2.4-21.6; and 17.5 pp., 95% CI 11.5-23.6, respectively); they also reported more performance degradation (PD 24.1 pp., 95% CI 17.0-31.2; 19.8 pp., 95% CI 14.1-25.6; and 14.8 pp., 95% CI 8.0-22.6, respectively). Weekly alcohol consumers reported more performance problems owing to cold (PD 18.2 pp., 95% CI 13.9-22.6) than non-consumers of alcohol. Cardiac and circulation symptoms were more common in women than men (PD 10.0 pp., 95% CI 1.1-18.9; and 8.4 pp., 95% CI 0.5-16.4, respectively). The age trend in performance issues was curved, with the highest prevalence among those aged 35-44 years, while the oldest workers (45-57 years) perceived less cold-related symptoms, particularly thirst. CONCLUSIONS: Cold-related symptoms and performance degradation were found to be common in this industry, with vulnerable groups comprising of highly educated workers, forklift drivers, storage and manufacturing workers, weekly alcohol consumers, aging workers, and women. The results demonstrate a need for further research on the adequacy of protection provided against the cold, particularly given that global warming will increase the contrast between cold workplaces and outdoor heat.